PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII6 SMP NEGERI 20 PEKANBARU - Septiastuti, Andita Septiastuti; Murni, Atma Murni; ', Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase learning process and students’ math achievement at class VIII6 SMPN 20 Pekanbaru through the implentation realistic mathematics education approach in cooperative learning model of STAD. The subject were 40 students from class VIII6 SMP Negeri 20 Pekanbaru consist of 17 male and 32 female students with the heterogeneus level. This study used classroom action research The instruments of data collection in this research were observation sheets and students Mathematic tests. The data which collected were analyzed with descriptive analyzed statistically. From analyzed of teacher and students activity in the learning process showed an improvement of learning process prior to the action on the first and second cycle. The result of this research showed an increasing number of students’ math achievement from the basic score 37.5% to 50% on the first daily test and 62.5% on the second daily test. Based on the result of this research can be concluded that the implentation realistic mathematics education approach in cooperative learning model of STAD can improve students’ math achievemsent at class VIII6 SMPN 20 Pekanbaru in the second semester academic years 2013/2014. Key Word : Students’ Math Achievement, Realistic Mathematics Education, Cooperative Learning Model of STAD, Classroom Action Research.